Citra Merek, Suasana Toko, dan Kualitas Produk terhadap Loyalitas Konsumen - Ahmad Hanafi; Retno Endah Supeni; Pawestri Winahyu (Institut Penelitian Matematika Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to determine and analyze the relevance of brand image, store atmosphere, and product quality to consumer loyalty. This research method uses a descriptive method with a quantitative approach. The sampling technique used is the purposive sampling method. Data collection techniques using observation and questionnaires. The analysis used is validity test, reliability test, multiple linear regression analysis, normality test, multicollinearity test, heteroscedasticity test, t test, and coefficient of determination. The results showed that the brand image variable (x1) on the consumer loyalty variable (y) has a significance level (α) of the brand image variable (x1) is 0.000 <0.05. The store atmosphere variable (x2) on the consumer loyalty variable (y) has a significance level (α) of the store atmosphere variable (x2) is 0.244 > 0.05. The results of the heteroscedasticity test using a scatterplot, the Product Quality variable (X3) on the Consumer Loyalty variable (Y) has a significance level (α) of the product quality variable (X3) is 0.006 < 0.05. In conclusion, store atmosphere has no significant effect on consumer loyalty, while brand image and product quality have a positive and significant effect on consumer loyalty, and simultaneously have a significant effect on consumer loyalty. Keywords: Brand Image, Store Atmosphere, Product Quality, and Consumer Loyalty